Characterization of shale formation of abandoned petroleum wells and treatment using acid simulation technique - Abdou, Saleh Mahmoud; Ali, Nabila Amin; Balboul, Mohamed Rajaa (Technology audit and production reserves, 2021)
The object of research is shale, which is a combination of carbonate (calcite or dolomite), and non clay minerals such as silica (quartz) and clay minerals such as kaolinite. Characterization of various minerals in shale formed in six abandoned petroleum wells was done using Energy Dispersive X-ray (EDX), X-ray diffraction (XRD) and Fourier Transformation Infra-Red (FTIR). Shale may contain a wide variety of minerals. The shale formation within the abandoned wells in the current study is at a deep of about (2600±300) meters. Three shale formation samples were collected from each of the abandoned wells. Characterizing the constituents of the clay minerals of the shale is important in the drilling and the treatment process. The analyses declared that, some shale formation samples are similar. The study was continued on three abandoned petroleum wells (I, II and III). The XRD and FTIR obtained results of shale analysis show the existence of calcite (CaCO3) and quartz (SiO2) in the shale samples. Dolomite CaMg(CO3)2 is present in well (II) and well (III), and muscovite H2KAl3Si3O12 is present in well (I). Also, Kaolinite Al2Si2O5(OH)4, and barite (BaSO4) components are detected in the FTIR results. Mg, K, Al and Ba trace elements are detected by EDX analyses and may contribute chemically. Shale technology and research development is concern with three steps: Characterization, simulation, and permeability stimulation. The present study focusing on the characterization and simulation of the shale formed in six abandoned (non-producing) petroleum wells for enhancing the productivity of carbonate reservoirs.